Synergetics of Nuclear Breeding Systems - Gordon, William Charles (My University, 1979)
The role of nuclear energy systems while produce fissile materials has become an important and essential part of scenarios for the future development of nuclear energy. Definitive analyses and nucleonic comparisons of these breeder systems have been impeded by the lack of a rigorous and consistent methodology for describing fissile fuel production and fertile fuel utilization. The research reported here therefore addresses itself to this problem and is based on a synthesis of three concepts: (1) the lumped parameter formulation of reactor physics, (2) the establishment of symbiotic relationships between breeders and converters and (3) the use of material stockpile inventories.
In the lumped parameter synergetic analysis the temporal variation of stockpile inventories and net electrical output of a selected system are established. The system is taken to consist of a general breeder reactor coupled to a fission converter reactor and fuel reprocessing-fabrication plant. By including the converter and processing plant and examining the temporal and nuclear behaviour of the entire system, various types of nuclear breeders can be analysed and subjected to a comparative analysis in a consistent manner. The use of lumped parameters, based on the integration of detailed space and energy dependent effects into single-valued parameters, has facilitated survey calculations and analysis of the conceptual systems defined herein. The temporal variation of the stockpile inventory is used to describe fissile fuel production and fertile fuel utilization since information, such as minimum inventory requirements and material replacement times, is provided. This approach eliminates the ambiguities involved in a single figure of merit description, such as, for example, the doubling time, and includes pre-steady-state effects and reprocessing lags and losses. To assess the net electrical production of the system, the consumption of electricity by the reactors and the processing plant is explicitly included.
The synergetics of fast-fission, symbiotic fusion, hybrid fusion and spallation breeders are then investigated. In these analyses, the fissile and fertile inventories and power output are calculated over the system lifetime for a specific breeder power. The effects on the system inventories of varying breeder thermal power are also examined. Since the mathematical-physical formulations are specified in terms of lumped parameters, the results of changing these on the system can be easily dealt with. Four fissile fuel breeding systems are then compared using current economic data.
On the basis of this study, it is evident that there exists no single breeder system which consistently outperforms the others in all aspects. The fast-fission breeder, while not a good fissile fuel producer, has the best power generating efficiency and, due to its relatively low capital costs, can produce electricity at the lowest cost. The symbiotic fusion breeder system has the shortest fissile fuel replacement time and requires less initial fuel investment but it produces electricity at the highest cost. For combined fissile fuel production and electrical generation, the hybrid fusion breeder excells and it is also a good conserver of fertile fuel. The spallation breeder outranks all others in fissile fuel production.
While no single breeder was found to be superior in a general sense, the synergetics method of analysis has been shown to be effective in several specific respects. The temporal variations of the stockpile inventories and net power derived here have a physically reasonable basis and are mathematically tractable. The pre-steady-state effects can be described with great accuracy by two functions determined by the fuel management scheme. Processing lags and losses are also explicitly incorporated. The flexibility and usefulness of the developed methodology are enhanced by the fact that any material stockpile inventory in the system can be calculated. Essential to this procedure is the inclusion at the outset of all system components in a synergetic analysis.
Keywords: Nuclear Engineering; Nuclear Engineering